Gordius gonzalezi, a new species of horsehair worms (Nematomorpha) from Spain - Schmidt-Rhaesa, Andreas; Martínez, Jesús (Zootaxa, 2016)
A new species, Gordius gonzalezi, is described from the Iberian Peninsula, from the Sierra de los Tormantos in Central Spain. Characteristic for the species is the presence of multiple short spines on the cuticle, not present in this form in any other Gordius species. Additionally, two further specimens are reported, which could not be determined to species level. One male of the genus Gordius is close to G. aquaticus and one female with regular areoles could belong either to the genus Gordius or to Gordionus.